2019
DOI: 10.1155/2019/5159094
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Numerical Analyses of Basalt Fiber Crumb Rubber Mortars in Soft Rock Roadways

Abstract: The strength of crumb rubber mortars can be improved by the addition of basalt fibers. However, limited studies have been conducted on basalt fiber crumb rubber mortars (BF-CRM), and the constitutive model is still very immature. In this paper, uniaxial compressive stress-strain curves are obtained for several groups of BF-CRM specimens with different contents. By comparison with the GZH model, modified GZH parameters that can be used in a BF-CRM constitutive model are obtained. Then, taking the support scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…For A2, B2, C2, and D2, the yield states appeared when the s were about 2-2.5%, while there were no peak strengths in group E. A comparison of the stresscurves in four groups A, B, C, and D indicated that as rubber particle content increased (from A to group D), the peak strengths exhibited a noticeable decrease, and the downtrend of stresse the peak strength became increasingly gentle. In addition, the maximum yield strengths were re when the mass fraction of basalt fiber was 0.4%, which was consistent with the results of the un compression test obtained by Qin et al [27].…”
Section: Triaxial Test Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…For A2, B2, C2, and D2, the yield states appeared when the s were about 2-2.5%, while there were no peak strengths in group E. A comparison of the stresscurves in four groups A, B, C, and D indicated that as rubber particle content increased (from A to group D), the peak strengths exhibited a noticeable decrease, and the downtrend of stresse the peak strength became increasingly gentle. In addition, the maximum yield strengths were re when the mass fraction of basalt fiber was 0.4%, which was consistent with the results of the un compression test obtained by Qin et al [27].…”
Section: Triaxial Test Resultssupporting
confidence: 91%
“…In Figure 4b, the rubber granular concrete B1 was seriously damaged compared to BFRGCs (B2, B3, and B4). Therefore, the addition of basalt fibers could inhibit the development of fractures in both plain concrete and rubber granular concrete, which was consistent with the results under uniaxial compression tests [27]. Moreover, the samples of B2-B4, C2-C4, D2-D4, and E2-E4 had no obvious failure.…”
Section: Triaxial Test Resultssupporting
confidence: 85%
See 3 more Smart Citations